The level of anxiety and depression in children and adolescents with chronic pain syndrome (on the example of juvenile idiopathic arthritis) - A. V. Santimov; V. G. CHasnyk; S. V. Grechanyi (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
In order to study the effect of anxiety and depression on the severity of chronic pain syndrome, 216 patients with the diagnosis of juvenile idiopathic arthritis (JIA) were examined. All children included in the study underwent a traditional rheumatological examination, with an assessment of the disease activity, and a psychometric assessment of the severity of pain, anxiety and depression. Comparison of various clinical groups showed significantly higher levels of severity of anxiety and depression in the case of chronic pain syndrome regardless of the presence of active or inactive phase of JIA, which confirms the necessity of using evidence-based psychological interventions such as relaxation techniques and cognitive behavioral therapy in all patients with JIA suffering from pain.